숯 제조시설의 악취물질 배출특성과 관리실태 조사 연구 - 정주영; 서병량; 김재혁; 진성민; 정종수 (한국환경과학회, 2012)
Emission characteristics of gaseous odor compounds emitted from the charcoal manufacturing process were investigated, and evaluated the odor removal efficiency of odor control devices. It was found that the measured odor dilution ratio of emission gases ranged from 10,000 to 44,814, which exceed largely the emission standard in the stack. Methylmercaptan, trimethylamine, hydrogen sulfide, acetaldehyde were turned out as major odor compounds of the charcoal manufacturing process. It was revealed that the odor removal ratio of odor control devices were very low due to the its improper maintenance and wrong design.